What is the answer to 3d+8=2d-17

Answers

Answer 1
Answer:  the answer to 3d+8=2d-17 is

d=-25



Related Questions

-2 (x-7)=-(2x+5) solve for x
The 162-room BeeGee Hotel, located just outside Philadelphia, Pennsylvania, requires room attendants to clean 18 rooms per day. If the hotel is forecasting a full house next Monday, how many guest room attendants will be needed to cover the day's cleaning tasks?
The ratio 3/8 to 4/9 has a unit rate of 1/6 true or false
What is the formula for the area of a rectangle?
Subtract 5 from the sum of 8.2 and 0.072?

0.00057 asa scientific notation

Answers

The scientific notation of the number 0.00057 is,

⇒ 5.7 × 10⁻⁴

We have to give that,

A number is,

⇒ 0.00057

Since Scientific notation is a way of writing very large or very small numbers.

For example; 230,000,000 can be written in scientific notation as

2.3 x 10⁸

Hence, Write the number in scientific notation as,

⇒ 0.00057

⇒ 5.7 × 10⁻⁴

To learn more about scientific notation visit:

brainly.com/question/1767229

#SPJ6

0.00057 written in scientific notation would be 5.7 * 10^(-4).
Hope that helped! =)

Given the function f(x) = x2 and k = 2, which of the following represents a horizontal shift? A. f(x) + k B. kf(x) C. f(x + k) D. f(kx)

Answers

Theere are certain rules that apply:
1. f(x)+k = vertical shift
2. kf(x) = vertical stretch/shrink (depending)
3. f(x+k) = phase shift, also known as a horizantal shift.
4. f(kx) = Horizantal stretch/shrink

The answer to your question is C. 
I hope that this is the answer that you were looking for and it has helped you.

Answer:

C

Step-by-step explanation:

i wouldnt lie to you

What's the value of log2 (1/8) ?

Answers

log_aa^p=p\n------\n\nlog_2 ( (1)/(8) ) =log_28^(-1)=log_2(2^3)^(-1)=log_22^(-3)=-3\n\nAns.\ -3

The correct answer for the value log_(2)(1)/(8)   is equal to -3.

What is Logarithm?

In mathematics, Logarithms are defined a  way of expressing exponents. A logarithm is defined as the power to which a number must be raised to get some other values.

The expression for logarithm of a number is written as ㏒ₓb = y.

Properties of Logarithm:

log_(x) (x^n) = n

The value of log_(2)(1)/(8) can be calculated by recognizing that (1)/(8) is equal to 2 raised to the power of -3.

log_(2)(1)/(8)   = log_(2)(2^(-3))

From the property of logarithm:

log_(2)(2^(-3))

= -3

The value of  log_(2)(1)/(8) is -3.

Learn more about Logarithm here:

brainly.com/question/30226560

#SPJ6

Let f(x)=4x-1 and g(x)=2x^2+3. Perform each function operations and then find the domain.1. (f+g)(x)   2. (f-g)(x)   3. (g-f)(x)   4. (f times g)(x)    5. f/g(x)   6. g/f(x)

Answers

The domain of a function is the set of input values, the function can take.

The values of the composite functions are:

\mathbf{(f + g)(x) = 2x^2 + 4x +2}

\mathbf{(f - g)(x) = -2x^2 + 4x - 4}

\mathbf{(g - f)(x) = 2x^2 - 4x + 4}

\mathbf{(f * g)(x) = 8x^3 - 2x^2 -12x + 4}

\mathbf{(f / g)(x) = ((4x - 1 ))/((2x^2 - 3))}

\mathbf{(g / f)(x) = (2x^2 - 3)/(4x - 1 )}

The functions are given as:

\mathbf{f(x) = 4x - 1}

\mathbf{g(x) = 2x^2 + 3}

\mathbf{(1)\ (f + g)(x)}

This is calculated as:

\mathbf{(f + g)(x) = f(x)+ g(x)}

So, we have:

\mathbf{(f + g)(x) = 4x - 1 + 2x^2 + 3}

Collect like terms

\mathbf{(f + g)(x) = 2x^2 + 4x - 1 + 3}

\mathbf{(f + g)(x) = 2x^2 + 4x +2}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(2)\ (f - g)(x)}

This is calculated as:

\mathbf{(f - g)(x) = f(x) - g(x)}

So, we have:

\mathbf{(f - g)(x) = 4x - 1 - 2x^2 - 3}

Collect like terms

\mathbf{(f - g)(x) = -2x^2 + 4x - 1 - 3}

\mathbf{(f - g)(x) = -2x^2 + 4x - 4}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(3)\ (g - f)(x)}

This is calculated as:

\mathbf{(g - f)(x) = -(f - g)(x) }

So, we have:

\mathbf{(g - f)(x) = 2x^2 - 4x + 4}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(4)\ (f * g)(x)}

This is calculated as:

\mathbf{(f * g)(x) = f(x) * g(x)}

So, we have:

\mathbf{(f * g)(x) = (4x - 1 )* (2x^2 - 3)}

\mathbf{(f * g)(x) = 8x^3 - 2x^2 -12x + 4}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(5)\ (f /g)(x)}

This is calculated as:

\mathbf{(f /g)(x) = (f(x) )/(g(x))}

So, we have:

\mathbf{(f / g)(x) = ((4x - 1 ))/((2x^2 - 3))}

There are restrictions to the value of x.

So, the domain is: \mathbf{(-\infty,-\sqrt{(3)/(2)} ) \ u\ ( -\sqrt{(3)/(2)},\sqrt{(3)/(2)}})\ u\ (\sqrt{(3)/(2)},\ \infty)}

\mathbf{(6)\ (g /f)(x)}

This is calculated as:

\mathbf{(g /f)(x) =1 / (f(x) )/(g(x))}

So, we have:

\mathbf{(g / f)(x) = (2x^2 - 3)/(4x - 1 )}

There are restrictions to the value of x.

So, the domain is: \mathbf{(-\infty, (1)/(4))\ u\ ((1)/(4),\infty)}

Read more about domain at:

brainly.com/question/21853810

f(x) = 4x - 1
g(x) = 2x² + 3

1. (f + g)(x) = (4x - 1) + (2x² + 3)
    (f + g)(x) = 2x² + 4x + (-1 + 3)
    (f + g)(x) = 2x² + 4x + 2
    Domain: {x| -∞ < x < ∞}, (-∞, ∞)

2. (f - g)(x) = (4x + 1) - (2x² + 3)
    (f - g)(x) = 4x + 1 - 2x² - 3
    (f - g)(x) = -2x² + 4x + 1 - 3
    (f - g)(x) = -2x² + 4x - 2
    Domain: {x|-∞ < x < ∞}, (-∞, ∞)
3. (g - f)(x) = (2x² + 3) - (4x - 1)
    (g - f)(x) = 2x² + 3 - 4x + 1
    (g - f)(x) = 2x² - 4x + 3 + 1
    (g - f)(x) = 2x² - 4x + 4
    Domain: {x| -∞ < x < ∞}, (-∞, ∞)

4. (f · g)(x) = (4x + 1)(2x² + 3)
    (f · g)(x) = 4x(2x² + 3) + 1(2x² + 3)
    (f · g)(x) = 4x(2x²) + 4x(3) + 1(2x²) + 1(3)
    (f · g)(x) = 8x³ + 12x + 2x² + 3
    (f · g)(x) = 8x³ + 2x² + 12x + 3
    Domain: {x| -∞ < x < ∞}, (-∞, ∞)

5. ((f)/(g))(x) = (4x - 1)/(2x^(2) + 3)
    Domain: 2x² + 3 ≠ 0
                         - 3  - 3
                        2x² ≠ 0
                         2      2
                          x² ≠ 0
                           x ≠ 0
                  (-∞, 0) ∨ (0, ∞)

6. ((g)/(f))(x) = (2x^(2) + 3)/(4x - 1)
    Domain: 4x - 1 ≠ 0
                      + 1 + 1
                        4x ≠ 0
                         4     4
                         x ≠ 0
                (-∞, 0) ∨ (0, ∞)

The volume of a box with a rectangular base is 3 072cm3.the length of the sides are in the ratio 1:2:3. Calculate the length of the shortest side.

Answers

(1) The volume of a box with a rectangular base is 3072 cm³...

X x Y x Z = 3072 cm³

(2) The length of the sides are in the ratio 1:2:3

This means that:

(X)*(2X)*(3X) = 3072 cm³

It also means that:

Y=2X

Z=3X

(3) Calculate the length of the shortest side...

(X)*(2X)*(3X) = 3072 cm³

6X³ = 3072 cm³

X³ = (3072 cm³)/6

X³ = 512 cm³

X = ∛(512 cm³)

X = 8 cm

----------

Answers:

Length of the shortest side (X): 8 cm

Length of the side (Y): 16 cm

Length of the side (Z): 24 cm

A monster truck tire will travel will travel 12.56 ft in one revolution. What is the radius of the tire?

Answers

If it travels 12.56 ft in one revolution, then the circumference of the tire is 12.56 ft.
Circumference = 2 x π x radius
12.56=2 x 3.14 x radius
radius x 6.28=12.56

Radius= 2 ft

Hope this helps :)
1 revolution
the part that touches the ground makes 1 full circle
therefor 12.56 is the cirvmerncere
circumfrence=2pir
12.56=circumfrence
12.56=2pir
divide both sides by 2
6.28=pir
aprox pi to 3.14 and divide both sides by 3.14
2=r

radius=2 feet